Single-Use vs. Reusable Digital Flexible Ureteroscope to Treat Upper Urinary Calculi: A Propensity-Score Matching Analysis - Huang, Fang; Zhang, Xiaoqiong; Cui, Yu; Zhu, Zewu; Li, Yongchao; Chen, Jinbo; Zeng, Feng; Li, Yang; Chen, Zhiyong; Chen, Hequn (Frontiers in Surgery, 2022)
Abstract Objective: The purpose of this research was to compare the treatment outcomes and costs of a single-use and reusable digital flexible ureteroscope for upper urinary calculi. Methods: 440 patients with reusable digital flexible ureteroscope and 151 patients with single-use flexible digital ureteroscope were included in this study. Through exclusion and inclusion criteria and 1:1 propensity-score matching analysis based on baseline characteristics, ultimately, 238 patients (119:119) were compared in terms of treatment outcomes. The cost analysis was based on the costs of purchase, repair, and reprocessing divided by the number of all procedures in each group (450 procedures with reusable digital flexible ureteroscope and 160 procedures with single-use digital flexible ureteroscope). Results: There was no statistical significance in mean operation time (P= 0.666). The single-use digital flexible ureteroscope group has a shorter mean length of hospital stay than the reusable digital flexible ureteroscope group (P=0.026). And the two groups have a similar incidence of postoperative complications (P=0.678). No significant difference was observed in the final stone-free rate (P=0.599) and the probability of secondary lithotripsy (P=0.811) between the two groups. After 275 procedures, the total costs of a single-use flexible ureteroscope would exceed the reusable flexible ureteroscope. Conclusion: Our data demonstrated that the single-use digital flexible ureteroscope is an alternative to reusable digital flexible ureteroscopy in terms of surgical efficacy and safety for upper urinary calculi. In terms of the economics of the two types of equipment, institutions should consider their financial situation, the number of FURS procedures, the volume of the patient's calculus, surgeon experience, and local dealerships' annual maintenance contract when making the choice.